(untitled) (Research, Society and Development, 2021)
Recently declared as Intangible Heritage of Brazilian Higher Education, by Law Project No. 4613 of 2019, the Rondon Project, developed by the Ministry of Defense, in partnership with state, municipal and public and private Higher Education Institutions (IES), the objective is to contribute to the formation of the university students as citizens and sustainable development in poorly assisted communities. In this sense, the present work reports the experience of students and professors of the University of José do Rosário Vellano-UNIFENAS, Alfenas campus, resulting from the participation in Operation Vale do Acre developed between July 08-17, 2019, in the city of Acrelândia-AC. Twenty-nine workshops were held, with themes related to Communication, Work and Production, Environment and Technology, and 2.148 people were trained, highlighting the participation of children, adolescents - young people, adults and the elderly, as well as the mass participation of the rural population, predominantly female.